Сравнительное изучение степени развития признаков у животных различного возраста и размера - Песков, В.Н. (Вестник зоологии, 1993)
Degree of a morphological character development can be estimated on the base of relative value: Xi = (Xi/Xi)-XG, where Xi and Xi— relative and absolute values of a character x in i-th individual; Xi and X0 — general size of i-tli individual and standard. Any individual or mean value of a studied subject general size can be used as a standard (X0). Proposed method is compared with index method and regression analysis, its application is exemlified by herpetological and theriological practice.